Upaya Upaya Mereduksi Perilaku Delinkuen melalui Peningkatan Persepsi Positif terhadap Iklim Sekolah - Fitria, Yuli (Fakultas Teknik, Universitas Bangka Belitung, 2023)
Delinquent behavior is a problem that is often carried out by adolescent students which is shown in the form of behavior against or contrary to rules, social norms that apply both at school and in society. One form of delinquent behavior is brawls between schools which are usually dominated by male students, such as in vocational high schools (SMK). This is a problem that always arises so that a solution must be immediately sought. Service activities in the form of outreach in the form of education about the dangers of delinquent behavior and measuring perceptions of school climate are carried out as an effort to reduce them. The stages of implementing this activity include; identification, preparation, implementation and evaluation. The results of the activity showed that there was a significant impact on students' understanding and perceptions of the school climate by 84% identified as having positive perceptions. It can be concluded that by forming positive perceptions and creating a conducive school climate, it can be used as a medium to minimize or reduce forms of violations at school, such as delinquent behavior.